1994
DOI: 10.1128/mcb.14.8.5569
|View full text |Cite
|
Sign up to set email alerts
|

The GTS1 gene, which contains a Gly-Thr repeat, affects the timing of budding and cell size of the yeast Saccharomyces cerevisiae.

Abstract: A gene with an open reading frame encoding a protein of 417 amino acid residues with a Gly-Thr repeat was isolated from the yeast Saccharomyces cerevisiae by using synthetic oligonucleotides encoding three Gly-Thr dimers as probes. The deduced amino acid sequence showed partial homology to the clock-affecting gene, per, of Drosophila melanogaster in the regions including the GT repeat. The function of the gene, named GTS1, was examined by characterizing the phenotypes of transformants with different copy numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 54 publications
(50 reference statements)
0
64
0
Order By: Relevance
“…Also, the period length of this oscillation was temperature independent, indicating a clock function [22]. In addition, a mutant in which the GTS1 gene, which has homology to period genes in other organisms [36] was deleted, produced a shortened period, about 20 min, with a destabilization in the amplitude of the oscillation every 11 h [34].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the period length of this oscillation was temperature independent, indicating a clock function [22]. In addition, a mutant in which the GTS1 gene, which has homology to period genes in other organisms [36] was deleted, produced a shortened period, about 20 min, with a destabilization in the amplitude of the oscillation every 11 h [34].…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting of carboxypeptidase Y (CPY) and alkaline phosphatase (ALP) was performed as described previously 43 using anti-CPY and anti-ALP antibodies (Molecular Probes, Eugene, OR, USA).…”
Section: Western Blottingmentioning
confidence: 99%
“…We subsequently found that the repeat was translated as an Ala-Gln repeat in the GTS1 product Gts1p [20], which is similar to the Gln-rich domain found in the clock-related protein Clock [21]. Although the structural basis of Gts1p as a clockrelated protein is obscure, mutations of GTS1 showed pleiotropic effects on yeast in a gene-dosage-dependent manner; these effects included the timing of budding and sporulation and the capacity for heat tolerance [19,22], all of which are known to be clock-related in other organisms (reviewed in [23,24]). Further, we found that the amplitudes and durations of the cyanide-induced ultradian oscillation changed significantly as a function of the GTS1 gene dosage, whereas the frequencies of oscillation did not vary very much among the stains tested [25].…”
mentioning
confidence: 99%
“…The gene GTS1 was originally isolated from a yeast cDNA library with oligonucleotides encoding three Gly-Thr repeats which had been found in the clock-related gene period [18] and was thus named GTS1 [19]. We subsequently found that the repeat was translated as an Ala-Gln repeat in the GTS1 product Gts1p [20], which is similar to the Gln-rich domain found in the clock-related protein Clock [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation